An effective experimental and numerical approach to dye UHMWPE fibers by synergetic disperse dyestuffs blends - Oumaima Amara; Debbabi Faten; Nizar Meksi; Hatem Dhaouadi (Journal of Engineered Fibers and Fabrics)
High-performance fibers, particularly UHMWPE (Ultra-High Molecular Weight Polyethylene), are widely used in the textile industry due to their remarkable mechanical and chemical properties. However, their inherent inertia to conventional dyes, known as challenging coloration, has led to ongoing research to enhance their dyeing affinity without the use of insoluble pigment dyes. This research introduces an innovative dyeing approach to enhance the clean dyeing efficiency of UHMWPE fibers. The approach involves utilizing a mixture of eco-labeled elementary disperse dyes to develop a cleaner dyeing process. A mathematical model was developed to meticulously select appropriate elementary disperse dyes based on their dyeing performances. This led to the determination of a global color quality index using desirability functions. By utilizing this technique, four yellow, four red, and five blue eco-labeled elementary disperse dyes were selected to create the yellow, red, and blue synergetic blends dye, respectively. The implementation of this innovative clean dyeing process resulted in significant improvements in both dyeing yield and dyeing fastness compared to traditional processes that use individual disperse dyes.